PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS GAME EDUKASI QUIZIZZ PADA MATA PELAJARAN PENATAAN PRODUK KELAS XI PEMASARAN SMKN 1 SOOKO MOJOKERTO - Fahrezi, Muhammad Gibran; Sulistyowati, Raya (Jurnal Pendidikan Tata Niaga (JPTN), 2025)
This study aims to develop an educational game-based learning medium using Quizizz for the Product Display subject in Grade XI Marketing at SMK Negeri 1 Sooko Mojokerto. This research is a type of Research and Development (R&D) utilizing the ADDIE development model, which includes five stages: needs analysis, media design, product development, field implementation, and effectiveness evaluation. The study focuses on the development process, product validity, and student responses to the use of the media. Validation of the media was conducted through assessments by two experts—namely, a media expert and an evaluation expert. The results indicated that the media was highly feasible, with a feasibility percentage of 95% from the material expert and 91% from the media expert. Additionally, student response questionnaires showed a 99% approval rating, indicating that the developed media was considered "very engaging." It can thus be concluded that the developed media is both feasible and engaging for use in the learning process of Grade XI Marketing students.